Micro-Flexible-Surface Probe for Determining Spatially Heterogeneous Electronic Conductivity of Lithium-Ion Battery Electrode Films. Issue 10 (8th October 2021) - Vogel, John E.; Hunter, Emilee E.; Wheeler, Dean R.; Mazzeo, Brian A.
Abstract : Lithium-ion battery electrodes are generally made up of porous, thin films that are structurally heterogeneous on multiple length scales due to the manufacturing process. This in turn causes spatial variability in the electrical properties of the film. This work reports development of a low-cost, flexible probe for measurement of film conductivity and contact resistance to the current collector. When mounted on a moveable stage, the probe can quickly produce maps of electrode electrical properties at sub-millimeter resolution. Bulk conductivity and contact resistance are determined by inverting a 2D model of the experiment. The method is validated using a conductive silicone rubber placed on top of plain and corroded steel with significant contact resistance variation. Measurements on commercial quality electrode films, two cathodes and one anode, show statistically significant macro-variations in film properties perpendicular to the rolling direction and micro-variations throughout the film, variations that will impact electrode performance. The flexible-surface probe can be a significant tool to determine and minimize sources of variation in electrode manufacturing.